Kajian Persepsi Petani terhadap Dampak Diversifikasi Tanaman Hortikultura pada Ketahanan Pangan Rumah Tangga di Kabupaten dengan Risiko Kekeringan Tinggi - Yosevita Theodora Latupapua; Ebedly Lewerissa (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2024)
Background: Increasing droughts caused by climate change have significant impacts on the agricultural sector, particularly on household food security. Purposed: To examine farmers' perceptions of the impact of horticultural crop diversification as an adaptation strategy to improve food security in drought-prone areas. Research Method: A quantitative approach using a survey method based on questionnaires distributed to farmers involved in horticultural crop diversification. Household food security was measured using the Household Food Security Index (IKP), and linear regression analysis was used to assess the impact of crop diversification on food security. Results: Horticultural crop diversification can improve household food security, particularly in drought-prone areas. Social, economic, and agricultural resource access factors have a significant impact on food security, with access to agricultural resources having the greatest effect. The validity and reliability tests show that the instruments used in this study are valid and reliable. In addition, the normality, multicollinearity, and heteroscedasticity tests indicate that the data meet the assumptions required for regression analysis. This study concludes that horticultural diversification is an effective adaptation strategy in dealing with the impacts of climate change and improving household food security, with recommendations to increase access to agricultural resources and support crop diversification programs in drought-prone areas.